(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2023)
The Medical Termination of Pregnancy (MTP) Act of 1971 is a critical piece of legislation in India that legalizes abortions up to 20 weeks of gestation in certain circumstances. The act has undergone several amendments since its inception, with the most recent being in 2021. This article provides a comprehensive overview of the MTP Act and its recent amendments with current rules. The amendments introduced in 2021 include extending the upper limit for abortions from 20 to 24 weeks and beyond for specific indications as approved by medical board constituted under the act, redefining the pool of medical professionals who can perform abortions depending upon length of pregnancy, legalizing the MTP in any women due to contraceptive failure with her partner till 20 weeks, removing the requirement for a second medical opinion from 12 to 20 weeks of pregnancy, and strengthening the confidentiality and privacy of women seeking MTP. Beyond 24 weeks, the MTP was allowed by medical board in cases of severe foetal abnormalities. This change was made in response to the increasing demand for abortions beyond 20 weeks, particularly in cases where the foetus has severe abnormalities that are detected late in pregnancy. This editorial article discusses the implications of these amendments and their potential effect on the health and well-being of women in India. These changes are expected to have a positive effect on the health & well-being of women in India.